Oxidative Stress Induced by High Salt Diet-Possible Implications for Development and Clinical Manifestation of Cutaneous Inflammation and Endothelial Dysfunction in Psoriasis vulgaris - Ivana Krajina; Ana Stupin; Marija Šola; Martina Mihalj (MDPI AG, 2022)
Although oxidative stress is recognized as an important effector mechanism of the immune system, uncontrolled formation of reactive oxygen and nitrogen species promotes excessive tissue damage and leads to disease development. In view of this, increased dietary salt intake has been found to damage redox systems in the vessel wall, resulting in endothelial dysfunction associated with NO uncoupling, inflammation, vascular wall remodeling and, eventually, atherosclerosis. Several studies have reported increased systemic oxidative stress accompanied by reduced antioxidant capacity following a high salt diet. In addition, vigorous ionic effects on the immune mechanisms, such as (trans)differentiation of T lymphocytes are emerging, which together with the evidence of NaCl accumulation in certain tissues warrants a re-examination of the data derived from in vitro research, in which the ionic influence was excluded. Psoriasis vulgaris (PV), as a primarily Th17-driven inflammatory skin disease with proven inflammation-induced accumulation of sodium chloride in the skin, merits our interest in the role of oxidative stress in the pathogenesis of PV, as well as in the possible beneficial effects that could be achieved through modulation of dietary salt intake and antioxidant supplementation.